Gratitude: A Way of Teaching - Griffith, Owen M. (Rowman & Littlefield Publishers, 2016)
This valuable book will give educators solution-based methods and research-based resources to improve classroom culture, as well as enabling schools to elevate students’ engagement and academic achievement. In addition, activities will be provided that will help teachers improve their own lives as well as their students’ lives. Grounded in scientific research, this book will delve into numerous integral aspects of gratitude as it relates to education. In addition, this useful publication will feature success stories and step-by-step instructions to successfully implement gratitude in schools. Educators will also be shown how to combat materialism and entitlement with gratitude and altruism, how to help teenagers utilize gratitude successfully, as well as encouraging the entire families of our students to embrace gratitude and make it a permanent part of their lives. Finally, educators will be inspired to stay energized with gratitude throughout the school year.